MENGAPA WAJIB PAJAK MENGIKUTI TAX AMNESTY (STUDI KASUS DI SOLO) - Titik Setyaningsih; Antin Okfitasari (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2016)
Tax amnesty program was obtain to apply Republic Indonesia government regulation number 11 year 2016. The present study aims at providing why do tax payers take tax amnesty. This study used Case Study Research approach. A single case study approach was choosen because one data was enough to achieve the research objective. Data were gathered by questionnaire and semi-structured interview with tax payers in Solo Raya. The finding shows that comprehension of tax amnesty only can be understood three of tax payers, they take tax amnesty program by working together with tax consultant, and the problems are for arranging technical and minim for socialization become obstruction of tax amnesty realization. The limitation of this research is not using comparative case study. In addition, this research timming is limited. However this research raises the higher of leader or personal commitment to do tax amnesty program with the hope by increasing regular tax amnesty socialization, simplification of procedure tax amnesty for small business tax payers, also if tax amnesty results, the tax money, actually were used for public wealthy.